2005
DOI: 10.1038/sj.bmt.1704830
|View full text |Cite
|
Sign up to set email alerts
|

Value of surveillance blood culture for early diagnosis of occult bacteremia in patients on corticosteroid therapy following allogeneic hematopoietic stem cell transplantation

Abstract: Summary:Bloodstream infection (BSI) is a significant complication following allogeneic hematopoietic stem cell transplantation (allo-SCT). Corticosteroids mask inflammatory responses, delaying the initiation of antibiotics. We reviewed medical records of 69 allo-SCT patients who had been on 40.5 mg/kg prednisolone to investigate the efficacy of weekly surveillance blood cultures. A total of 36 patients (52%) had positive cultures, 25 definitive BSI and 11 probable BSI. Pathogens in definitive BSI were Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 27 publications
(25 reference statements)
1
33
1
2
Order By: Relevance
“…The incidence of positive blood cultures observed in this study corresponds with previously reported incidence of CVC-related infections and positive blood cultures in hematological patients ranging between 35% and 52% [1,2,4,5,7,13]. A lower number of patients with positive CVC blood cultures in the coated CVC group (45% vs. 36%, p =0.05), more repeatedly positive CVC blood cultures observed in the uncoated CVC group (26% vs. 8,6%, p =0.018), and highly significant difference in positive CVC blood cultures per 1,000 catheter-days (29 vs. 14, p=0.005) showed rather positive effect of the chlorhexidine/silver sulfadiazine-coated CVCs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The incidence of positive blood cultures observed in this study corresponds with previously reported incidence of CVC-related infections and positive blood cultures in hematological patients ranging between 35% and 52% [1,2,4,5,7,13]. A lower number of patients with positive CVC blood cultures in the coated CVC group (45% vs. 36%, p =0.05), more repeatedly positive CVC blood cultures observed in the uncoated CVC group (26% vs. 8,6%, p =0.018), and highly significant difference in positive CVC blood cultures per 1,000 catheter-days (29 vs. 14, p=0.005) showed rather positive effect of the chlorhexidine/silver sulfadiazine-coated CVCs.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to the microbiologically documented infections in patients before hematopoietic engraftment of only 5-10%, the focus of bacterial infection can be identified in more than 50% of patients after hematopoietic engraftment [3,11,14]. The incidence of CVC-related infections in hematological patients has been reported to range between 35% and 45% [1,4,5,13] and positive blood cultures have been found in 36-52% [2,7].…”
Section: Introductionmentioning
confidence: 95%
“…Other investigators, however, have shown that HCT recipients on corticosteroids may have a high incidence of occult bacteremia and may represent a group where SBCs might be of greater value. 23,24 In addition to the low overall frequency of positive SBCs and high frequency of these cultures being of questionable clinical significance, the costs associated with obtaining these cultures was not insubstantial. The time frame of obtaining weekly SBCs was chosen arbitrarily and was not based on any supporting evidence.…”
Section: Discussionmentioning
confidence: 96%
“…There is some evidence that SBCs may be useful in allo-HCT recipients during the initial preengraftment period of profound neutropenia and in patients receiving corticosteroids. 23,24 However, SBCs are not recommended in the absence of clinical signs and symptoms in immunocompetent individuals, and their utility has been questioned in some studies conducted in pediatric HCT recipients, especially those without neutropenia. 25,26 Currently, no guidelines exist for the management of asymptomatic patients with positive SBCs.…”
Section: Introductionmentioning
confidence: 99%
“…Common skin contaminants, such as diptheroids, Bacillus sp., Propionibacterium sp., coagulase negative staphylococci (CNS,) or micrococci required at least 2 consecutive blood cultures drawn on separate occasions to be defined as a true blood stream infection. 7,[9][10][11] If only a single isolate was positive, all of the following criteria were required for the diagnosis of definitive infection: the presence of central venous catheter; the initiation of antimicrobial therapy; and at least 1 of the following: temperature more than 38.01C or <36.01C; chills; or systolic blood pressure <2 SD below the normal for age. Otherwise the isolate was regarded as a probable contaminant.…”
Section: Definitionsmentioning
confidence: 99%